Accounting research in Brazil: bibliometric study of three journals (Revista Brasileira de Contabilidade e Gestão, 2012)
Scientific communication plays an important part in society, as it is a necessary mean for the publication of scientific production. In the periodicals, pieces of research that help to disseminate knowledge to the most diverse users are publicised. The research has as an objective to analyse the characteristics of all the articles of three national periodicals of accounting: “Revista Ambiente Contábil”, “Revista Sociedade Contabilidade e Gestão” and “Revista Contabilidade e Controladoria”. For that, it was used a bibliometric model to the collection of the characteristics of the articles observing the following variables: total of publicised articles, number of fascicles, amount of articles per fascicle, quantity of authors per article, total of references used and types of macro-themes. Regarding the characteristics of the authors it was observed: academic filiation and the category, titles, whereabouts of the authors and gender. Within the results, it is worth mentioning that approximately two thirds of the authors are male, in the periodicals “Sociedade” and “RC&C” there is a larger concentration of doctors whereas in the “Ambiente” a larger concentration of masters occurs. The most approached macro-theme was managerial accounting and there is a vaster concentration in the Southeast region. The analysed periodicals were compared to other similar sorts of works. It was observed that the publications in the three periodicals do not follow a tendency of the contemporary accounting.
Keywords: Jornal Contabilidade e Controladoria; bibliometry; cientific periodicals; Jornal Ambiente Contábil; Jornal Sociedade Contabilidade e Gestão